TYPES ACCORDING TO THE STRUCTURE OF THE SENTENCE - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
; This article describes the types of sentences according to the structure of the studied language, sentence formation and structures, and other word groups used in the sentence.